2020
DOI: 10.1177/2048872620914931
|View full text |Cite
|
Sign up to set email alerts
|

Acute type A aortic dissection: Aortic Dissection Detection Risk Score in emergency care – surgical delay because of initial misdiagnosis

Abstract: Background: Acute type A aortic dissection requires immediate surgical treatment, but the correct diagnosis is often delayed. This study aimed to analyse how initial misdiagnosis affected the time intervals before surgical treatment, symptoms associated with correct or incorrect initial diagnosis and the potential of the Aortic Dissection Detection Risk Score to improve the sensitivity of initial diagnosis. Methods: We conducted a retrospective analysis of 350 patients with acute type A aortic dissection. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 29 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…We conclude that focused ante-mortem attention is needed with regard to acute chest pain, and these patients must be evaluated to distinguish for example between acute coronary syndrome, pulmonary embolism, acute aortic syndrome, esophageal rupture, or tension pneumothorax [17]. Autopsy is a relevant quality improvement tool, and the presented data have relevant clinical impact [12,13,18]. Several studies have outlined the importance of autopsy for clinical practice and.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conclude that focused ante-mortem attention is needed with regard to acute chest pain, and these patients must be evaluated to distinguish for example between acute coronary syndrome, pulmonary embolism, acute aortic syndrome, esophageal rupture, or tension pneumothorax [17]. Autopsy is a relevant quality improvement tool, and the presented data have relevant clinical impact [12,13,18]. Several studies have outlined the importance of autopsy for clinical practice and.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic and technical progress in medicine have changed the conditions which lead to diagnostic discrepancies ante-and postmortem [23]. Lack of time for appropriate diagnostic tests can have a high impact on misdiagnoses [18,24]. Buschmann et al described cases of trauma-related death, where diagnostic assessment was limited due to short stay in the emergency room or required cardiopulmonary resuscitation [24].…”
Section: Discussionmentioning
confidence: 99%
“…Historic studies demonstrated a time-dependent increase in mortality, which led to the widely accepted practice of expediting emergent surgery as definitive treatment 6 . Nonetheless, numerous studies have shown that delays or errors in diagnosis continue to persist with relative frequency: one study reported the www.nature.com/scientificreports/ median time between a patient's arrival to the ED and diagnosis of ATAAD was 4.3 h, while others reported that delays in diagnosis occur in up to 25% of cases 7,10,[14][15][16]24,25,26 . Evangelista and colleagues analyzed 20-year IRAD data and reported an overall surgical mortality from ATAAD repair of 18%, while Lee and associates examined the STS registry and found operative mortality to be 17% 7,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Because concurrent cocaine use is a relatively rare feature among all aortic dissection cases, patients could be misdiagnosed due to cardiovascular genesis being more likely associated to cocaine use [ 4 ] . In the history-taking setting of a patient with acute chest pain in the emergency room, the use of drugs should be included in the differential diagnostic considerations and the diagnosis of acute aortic dissection should be considered [ 8 , 24 , 25 ] .…”
Section: Discussionmentioning
confidence: 99%